Bridging the gap between policy and practice: the Chilean case of adopting and implementing a psychosocial risk management regulation to protect and promote mental health at work - Munoz-Harrison, Miguel A. (2025)
In 2019, 970 million people worldwide experienced some type of mental burden during their lifespan; hence, mental ill-health has become one of the most concerning health problems across societies. To address this issue, international organisations have highlighted the need to adopt integral strategies that include aspects ranging from structural conditions that influence mental health to reducing the consequences of mental disorders. In this respect, employment is an important social determinant of mental health because it provides individuals with opportunities to develop socially and economically, along with determining the type of occupational risks employees are exposed to. Therefore, during the last decades the international community has made many calls for action to develop national programmes and policies to mobilise organisations to enhance working conditions, known as psychosocial factors, in order to protect and promote employees’ mental health. However, currently there is a global scarcity of countries that have introduced national policies and regulations regarding psychosocial risk management. Chile, through the publication of the ‘Protocolo de Vigilancia de Riesgos Psicosociales en el Trabajo’ (Psychosocial Risks at Work Surveillance Protocol in English) in 2013, is one of the few nations worldwide that has adopted this sort of legislation. Nevertheless, occupational mental diseases still show an upward trend in this country. This situation evidences a gap between policy and practice, in which governmental actions have not led to effective organisational initiatives in protecting and promoting mental health at work. Unfortunately, this issue has also been recorded in countries from the global north with a longer tradition of managing psychosocial risks. This thesis aim is to systematise and review the Chilean experience of adopting and implementing a psychosocial risk management regulation. Moreover, it addresses the overarching research question: ‘How have international values and scripts related to psychosocial risk management been adopted, legitimated and implemented in the context of Chilean society and enterprises?’ through a transdisciplinary approach that includes literature from public policy, organisational sociology, psychology, and management. Based on these conceptualisations, a multilevel, integral and bidirectional theoretical framework is proposed to bridge the gap between policy and practice. The current research is underpinned by a critical realism ontological and epistemological perspective. As such, the Chilean experience of adopting and implementing a psychosocial risk management regulation is framed as a case study reviewed under a qualitative approach. Data was collected with policy documents and semi-structured interviews, while their analysis involved triangulation and thematic analysis techniques. Furthermore, the Chilean experience was examined using three empirical studies. The first study reviews policy development aspects, including introducing psychosocial risk management to the policy agenda and the subsequent formulation, implementation, and consolidation of the Psychosocial Risks at Work Surveillance Protocol. The second study examines the elements that facilitate and hinder the legitimation of this regulation among social and organisational stakeholders. Lastly, the third study revolves around the experience of enterprises in managing psychosocial risks by complying with local legislation. Findings evidence several gaps that require attention for national initiatives to protect and promote mental health at work effectively. These include integrating psychosocial risk management with national and organisational needs and concerns, developing capabilities and infrastructure that support organisations in complying with this statutory obligation and evaluating the effects of national programmes and policies on psychosocial factors and employees’ mental well-being indicators. To address these gaps, this research suggests fostering vertical and horizontal collaboration between policymakers and other public and private actors. This approach would align stakeholders, roadmaps, infrastructure, resources, and capabilities required to improve the initiatives organisations conduct to enhance their psychosocial work environment. Overall, this thesis provides insights that are useful both for Chile and on a global scale. On the one hand, it underlines this country’s main strengths and areas for improvement regarding its national psychosocial risk management regulation. On the other hand, stakeholders worldwide can contrast findings from this research with their current situation about protecting and promoting mental health at work. Nevertheless, in this last case, they should be carefully read in accordance with local characteristics.